La microempresa y su responsabilidad social: caso ISA en Morelia, México - Glafira Vázquez-Olarra; Ignacio Arroyo-Arroyo; Ameyalli Mitzi Gonzáles-Vázques; Eva Angelina Hernández-Oceguera (Mundo Fesc)
Corporate social responsibility is applicable to all business sizes. In order to implement a model for corporate social responsibility management that serves as the basis for sustainable actions that benefit the community, a qualitative study was conducted using action research. A micro-enterprise was involved in implementing corporate social responsibility strategies as part of its management. This was achieved through consulting with the entrepreneur and stakeholders. Individual and focus group interviews were conducted, applying a corporate social responsibility (CSR) management model. The limitation of the study is that the results cannot be replicated in an organization with similar characteristics, leadership style, and executive commitment. However, it demonstrates that a micro-enterprise can participate in CSR actions, contrary to the widely held notion that CSR can only be developed by large organizations. The company in question implemented a CSR management system, engaging stakeholders and actively participating in community development with its employees, students, competitors, and customers, thereby sharing its responsibility for the care of society.